2014
DOI: 10.3389/fpsyg.2014.00689
|View full text |Cite
|
Sign up to set email alerts
|

How does this make you feel? A comparison of four affect induction procedures

Abstract: Affect is a fundamental aspect of the human mind. An increasing number of experiments attempt to examine the influence of affect on other psychological phenomena. To accomplish this research, it is necessary to experimentally modify participants' affective states. In the present experiment, we compared the efficacy of four commonly used affect induction procedures. Participants (38 healthy undergraduate students: 18 males) were randomly assigned to either a pleasant or an unpleasant affect induction group, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 83 publications
4
61
0
Order By: Relevance
“…We used music and mental imagery via short stories to induce joy, relaxation, fear, or sadness in a between‐subject design. As in previous studies, the mood induction technique was successful, and a large proportion of the participants reported feeling the induced mood. Before discussing results in detail below, we highlight that all three color dimensions (hue, lightness, and chroma) contributed to explaining the match between mood and color, which was systematic.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We used music and mental imagery via short stories to induce joy, relaxation, fear, or sadness in a between‐subject design. As in previous studies, the mood induction technique was successful, and a large proportion of the participants reported feeling the induced mood. Before discussing results in detail below, we highlight that all three color dimensions (hue, lightness, and chroma) contributed to explaining the match between mood and color, which was systematic.…”
Section: Discussionsupporting
confidence: 70%
“…For example, “sad” music can be experienced as sad as well as pleasurable . When music is contextualized (e.g., with lyrics, mental imagery), the emotional ambiguity is reduced, and it becomes one of the most powerful and widely used techniques for mood induction . In such a mixed technique, participants listen to music and read short stories, which they are asked to actively imagine .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure can be used alone or combined with other mood induction procedures (Jallais & Gilet, 2010). Studies comparing different mood induction procedures have demonstrated the greater effectiveness of autobiographical recall relative to other approaches (Gilet, 2008;Jallais & Gilet, 2010;Zhang, Yu, & Barrett, 2014), especially when it is used to induce positive emotions (Strack, Schwarz, & Gschneidinger, 1985).…”
Section: Autobiographical Recall As a Mood Induction Proceduresmentioning
confidence: 99%
“…There was also a non-significant trend (p<0.1) for Pleasant but not Unpleasant room subjects to show a decrease in the PANAS scale measure of negative affect (NA) across test sessions. Overall, however, effects were very small even though similar affect manipulations have been used successfully in the past (sweet gift: [23, 27]); future studies might employ alternative manipulations such as use of affective images and music, and recall of affectively salient events [28]. In order to minimise the chances of subjects conforming to their expectations of how an emotion manipulation should affect their behaviour, we deliberately attempted to impose an implicit manipulation by not informing them about the presence of the two different rooms.…”
Section: Discussionmentioning
confidence: 99%